Somatic mutations in angiogenesis-related pathways and RNA polymerase II activity in sporadic brain arteriovenous malformations - Pérez-Alfayate, Rebeca; García-Barberán, Vanesa; Casado-Fariñas, Isabel; Hernández-Martínez, Desiré; Gómez del Pulgar, María E.; Castaño-Montoya, Juan Pablo; Pérez-Segura, Pedro; Cabezas-Camarero, Santiago (Frontiers in Neurology, 2025)
BackgroundSporadic brain arteriovenous malformations (bAVMs) are rare vascular anomalies characterized by abnormal angiogenesis and direct arteriovenous shunting. While the VEGF pathway is well studied, the genetic landscape contributing to angiogenic dysregulation remains poorly defined. We aimed to characterize the mutational profile of resected bAVMs using a pan-cancer next-generation sequencing panel, with particular focus on angiogenesis-associated pathways and RNA Polymerase II activity.MethodsA descriptive analysis of clinical and molecular characteristics was conducted In formalin-fixed, paraffin-embedded tissue from the bAVM nidus. DNA was extracted and sequenced using the Oncomine Tumor Mutational Load Assay, covering 409 cancer-related genes. Variants were filtered for pathogenicity, allele frequency, and functional relevance.ResultsThirteen sporadic bAVMs were retrospectively analyzed. Twelve pathogenic variants were detected in 7/13 (54%) patients, with variant allele frequencies ranging from 3.61 to 50.61%. Most mutations clustered within angiogenesis-related pathways (PI3K/AKT/mTOR, RAS/MAPK), DNA repair mechanisms, and transcriptional regulators of RNA Polymerase II. Notably, six mutations involved genes with known functional links to RNA Pol II activity. These findings suggest a converging role for transcriptional dysregulation and vascular remodeling in bAVM pathogenesis.ConclusionThis study proposes a novel hypothesis implicating RNA Polymerase II-mediated transcription in the aberrant angiogenesis of bAVMs. While KRAS mutations were detected at low frequency and allele burden, other genetic alterations in DNA repair and transcriptional machinery may drive or sustain vascular instability. Further functional validation is warranted to clarify their pathogenic role and therapeutic potential.